Exploring Primary Healthcare Nurses’ Preparedness and Response toward COVID-19 Pandemic in Makkah, Saudi Arabia: A Cross-sectional Study - Albishi, Amal; Mathkur, Amnah; Alshmemri, Mohammed; Alghabbashi, Maram (British Journal of Healthcare and Medical Research, 2022)
Background and aim: Nurses' responsibilities during this epidemic have broadened beyond simply caring for the ill to assisting them in their recovery. The main purpose of this study was to assess the primary healthcare nurses’ preparedness and response to COVID-19 pandemic in primary healthcare centers in Makkah- Saudi Aribia. Materials & Methods: A quantitative cross-sectional design was conducted at primary healthcare centers in Makkah. The population of the current study consisted of nurses who are working in primary healthcare in Makkah during the period of COVID-19. The total number of study sample is 132. Self-administered questionnaire was used to collect data from the participants adopted from Al Baalharith & Pappiya (2021). Results: The majority (92.4%) of participants have high knowledge, 4.5% of them have average knowledge, while 3.0% of them have weak knowledge. Moreover, the majority (93.9%) of nurses stated that health care workers explain the reason for triage/screening to patients and 92.4% of them stated that there was a designated screening area to check the temperature. Factors associated with nurses’ preparedness toward COVID-19 pandemic involve nurses’ knowledge of preparedness and nurses’ knowledge of preparedness and response. Conclusion: The nurses who participated in the study had a high level of awareness of pandemic preparedness and response. The level of readiness and preparation shown by nurses with regard to personal protective equipment is insufficient. Age, years of experience, and the setting in which nurses operate are all factors that influence their level of readiness knowledge.